1996
DOI: 10.1139/v96-239
|View full text |Cite
|
Sign up to set email alerts
|

Ionically conducting polyether composites

Abstract: Ionic conductivity in polymer-salt electrolytes occurs in the amorphous regions of the complex. Poly(ethy1ene oxide) (PEO) is the best polyether for complexing salts. Unfortunately, it is partially crystalline at ambient temperatures. With inorganic (i.e., alumina) or organic (i.e., poly(acry1amide) (PAAM)) fillers the crystallization of PEO is inhibited and the room temperature conductivity is enhanced in these mixed phase systems by over two orders of magnitude (to -lo4 Slcm) above the base PEOsalt system (<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Since PEO is known as a Lewis base and Li þ cation as a Lewis acid the phenomena occurring in composite electrolyte were explained in terms of equilibria between various Lewis acide base reactions occurring in the composite electrolyte systems. The same group [93] also substantiated that the ionic conductivity occurs only in the amorphous phase of the polymeresalt electrolyte system. The authors found in a system composed of both organic (polyacrylamide) and inorganic (Al 2 O 3 ) fillers that the inorganic filler increases the glass transition temperature and on contrary, organic filler reduces the glass transition temperature.…”
Section: Introductionmentioning
confidence: 70%
“…Since PEO is known as a Lewis base and Li þ cation as a Lewis acid the phenomena occurring in composite electrolyte were explained in terms of equilibria between various Lewis acide base reactions occurring in the composite electrolyte systems. The same group [93] also substantiated that the ionic conductivity occurs only in the amorphous phase of the polymeresalt electrolyte system. The authors found in a system composed of both organic (polyacrylamide) and inorganic (Al 2 O 3 ) fillers that the inorganic filler increases the glass transition temperature and on contrary, organic filler reduces the glass transition temperature.…”
Section: Introductionmentioning
confidence: 70%
“…composite polymer electrolytes (CPEs The CPEs offer some interesting features, for instance, good flexibility, high thermal stability, good interfacial contact and high ionic conductivity by enhancing ion mobility [16,32]. The electronic and ionic conductivities of CPEs depend on the characteristics of particles used, including the particles size, porosity, concentration, surface area and the interaction between the particles and the polymer matrices [63][64][65]. The enhanced electrochemical and mechanical properties of CPEs are important for their technological application in electrochemical devices.…”
Section: Composite Polymer Electrolytesmentioning
confidence: 99%
“…Previous studies have shown that the ionic conduction of CPEs depends on the characteristics of the particles used, such as size, porosity, surface area and functionality, concentration, and on the interaction between the particles and the polymer [23][24][25]. To clarify these issues, one should consider tailoring structural modifications by selecting inorganic fillers having appropriate chemical properties and by maximizing their surface area.…”
Section: Introductionmentioning
confidence: 99%